Chemical Composition of Essential Oil of Artemisia sieversiana from Tibet. Issue 5 (3rd September 2017) - Li, Hailiang; Pu, Junyan; Zeng, Liyan; Zhong, Yang; Xu, Fuli; Nan, Peng
Abstract: The essential oils isolated from the different parts of Artemisia sieversiana growing in Tibet were analyzed by GC-FID and GC-MS. Twenty-five components were identified representing 81.3 % of the essential oil from flower. The major components were chamazulene (24.1 %), α-bisabolol (23.5 %), and α-phellandrene (9.8 %). Thirty-six components were identified representing 88.3 % in the essential oil from the root, stem and leaf. The major components were α-bisabolol (45.4 %), chamazulene (21.9 %) and lavandulol (3.6 %). The results showed similarity in major components among different oils. Sesquiterpene hydrocarbons and oxygenated sesquiterpenes characterized all two studied oils. Our results suggest A. sieversiana in Tibet should be a great resource with the potential pharmaceutical value.